Land-leasing behavior, local officials’ promotions, and Chinese cities’ debt risks - Zhang, Lihua; Han, Rui; Zhang, Juanfeng; Li, Lele; Zhang, Danxia (International Journal of Strategic Property Management, 2021)
This study first analyzes how local governments’ land-leasing behaviors affect Chinese cities’ debt risk then examines the impact of officials’ promotion mechanisms on debt risk in China’s urban land bank system. The land-leasing behavior is reflected through three indicators, namely, land-leasing revenue, land-leasing scale, and land financial dependence level. Two new indicators are constructed to measure the local government’ debt risk from the perspective of debt scale and debt repayment: the debt scale risk and debt burden risk. Empirical analyses are based on the data of 281 prefecture-level cities from 2006–2015. The main findings are twofold. First, the debt scale risk is positively affected by the land-leasing revenue, and officials’ promotion pressure. The debt burden risk is positively affected by the land financial dependence and officials’ promotion pressure. Second, the officials’ promotion pressure significantly enhances the positive effect of land-leasing revenue on the debt scale risk. Local officials, who are under promotion pressure, are inclined to expand the size of urban investment bonds, which increases debt scale risk.